In the shadow of the Moon, what type of solar eclipse will we see?. (3rd April 2017) - Brown, Todd; Brown, Katrina
ABSTRACT: Solar eclipses occur several times a year, but most people will be lucky if they see one total solar eclipse in their lifetime. There are two upcoming total solar eclipses that can be seen from different parts of the United States (August 21, 2017 and April 8, 2024), and they provide teachers with an amazing opportunity to engage students with a remarkable astronomical event. We summarize the science behind eclipses and describe an inexpensive activity for students from third grade up through middle school that will let them use models to see the differences between total, annular, and partial solar eclipses. The activity lets students explore why, during a solar eclipse, people in different areas will see different types of eclipses. The activity can be used as a way to get students excited about astronomy and the upcoming eclipses. We also give ideas for ways that teachers can engage their students during the eclipses.